Design And Implementation Of Real-time Vehicle Speed Monitoring Device For Front And Rear Vehicles. Issue 1 (1st June 2022) - Wei, Conghao; Lin, Ni
Abstract: A real-time vehicle speed monitoring system is designed based on the millimeterwave radar sensor.This paper details the system design scheme, hardware composition and core algorithm.On this basis, the physical monitoring system is set up.After testing, the scheme design of the system is reasonable and feasible.Compared with the traditional car itself speed detection system, the system has the characteristics of simple structure, novel and easy to realize, and can be widely used in the future intelligent vehicle field.